STEM-Based Parabolic Motion Learning: AI-Assisted Video Development for High School Students - Lestari, Yora Indah; Siahaan, Sardianto Markos; Ismet, Ismet (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2025)
STEM learning is increasingly relevant in facing the challenges of 21st-century education. The use of technology, including artificial intelligence (AI), is expected to improve the effectiveness of the teaching and learning process. This study develops AI-supported STEM learning videos on parabolic motion for 11th-grade high school students. The methodology used follows the Alessi and Trollip model, which includes the stages of planning, design, expert validation, and practical testing. The methodology used follows the Alessi and Trollip model, which includes the stages of planning, design, expert validation, and practical testing. Initial practical testing scored 95%, and follow-up testing scored 94%. The N-gain value reached 0.57, categorized as effective. The findings indicate that the video is suitable for use in the learning process and is capable of improving students’ understanding of abstract concepts and motivating them. This study emphasizes the importance of integrating AI and STEM in the development of innovative learning media.